Pengaruh Suhu Pengeringan pada Pembuatan Tepung Umbi Bunga Dahlia - Raihana Amalia Novriza; Mutiara Dahlia; Ridawati Ridawati (Syntax Idea)
This study aims to make efforts to utilize dahlia flower tubers as an alternative food ingredient in the form of flour. The change that occurs from dahlia tubers to dahlia tuber flour is one of the efforts to expand its utilization into semi-finished products or finished products with a longer shelf life and maintained quality. In this way, the dahlia tubers can be utilized easily and optimally to be used as alternative food ingredients which can later be applied to various food preparations. The research method used was an experimental method by testing the manufacture of dahlia tuber flour. The research location is in the Food Processing Laboratory, Culinary Education Study Program, Faculty of Engineering, Jakarta State University. Results, In this study 1 kg of dahlia tubers were used to be processed into dahlia tuber flour. Furthermore, sorting was done to remove fresh tubers and tubers that were not fresh/rotten and obtained 900 grams of tubers. The conclusion is that the organoleptic quality of dahlia tuber flour with the use of drying temperature and the use of different meshes in the sieve produces significant differences in the aspects of color and level of fineness. As for the aspects of aroma, taste, and after taste, there was no significant effect on the manufacture of dahlia tuber flour.